Metis and reserve housing of Northern Saskatchewan a comparison of quality 1981-1991 - Beatch, Warren Thomas (1995)
This study investigates differences in the quality of housing stock between Indian Reserves and off-reserve Metis communities in Census Division #18 in northern Saskatchewan between 1981 and 1991. The hypothesis states that Census Division #18 reserve housing is in better condition than Census Division #18 off-reserve community housing. The purpose is to determine if differences exist, identify these differences and determine why they exist. A major problem for all northern Saskatchewan housing is its rapid deterioration rate, largely due to a lack of general maintenance practices and funds. Since the 1940's, Saskatchewan's northern population has shifted from a land-based nomadic lifestyle living in basic shelters to permanent settlements and modern housing. This has resulted in pressures on governments for social housing in northern Saskatchewan from both Treaty Indians and Metis people. Most Native northerners have been put into a position of dependency upon government for both their social and economic well-being. The two major social housing programs for northern Saskatchewan will be investigated to determine if they are major factors causing differences in housing quality between reserve and non-reserve communities. The 'Indian-on-Reserve' housing program is funded by the federal government and delivered. to reserves by Indian and Northern Affairs Canada. The 'Rural and Native Housing Program' for Metis communities is jointly funded by the Saskatchewan provincial government and the federal government, and delivered by the provincial government. As a result of differences in housing programs and funding between the two levels of government, sharp variations in the quality of housing stock exists between reserve and non-reserve communities in the same locale. Census Canada data from the 1980's and a 1991 micro study of Canoe Lake Reserve and the Metis community of Jans Bay are used to test the hypothesis that reserve housing is in better condition than non-reserve Metis housing. Two main methods are used: 1) ...